Comparison of the Activity for Theaflavin Production by a Recombinant Polyphenol Oxidase and a Commercial Enzyme - Zeng, Jun; Li, Yajie; Li, Feiyan; Zhou, Sisi (Synlett, 2024)
Theaflavins (TFs) contribute greatly to the color and flavor of black tea, and have various bioactivities beneficial to human health. This research compared the activity for TF production from tea polyphenols of recombinant polyphenol oxidase (Malus domestica, GenBank login number LT718523.1, MdPPO2) with that of commercial polyphenol oxidase (Agaricus bisporus, AbPPO) in both free and immobilized forms. Enzyme assays by LC-MS revealed that the production of TFs by the commercial enzyme AbPPO was almost five times as high as that of free recombinant MdPPO2. When immobilized on mesoporous silica, however, the activity of recombinant MdPPO2 increased significantly, whereas AbPPO almost lost its activity. In terms of the relative enzyme activity, the immobilized recombinant MdPPO2 had the highest relative enzyme activity, which was more than six times higher than that of free AbPPO. Among the TFs that were produced, TF3 was the most abundant, followed by TF2a, TF1, and TF2b.
Keywords: theaflavins; enzyme engineering; recombinant enzymes; polyphenyl oxidase; tea